EFISIENSI PEMASARAN BIBIT TANAMAN CABAI DI KELOMPOK WANITA TANI KARANG LESTARI DESA SIBANG KAJA - Si Ngurah Rai Putrajaya; I Made Tamba; Ni Putu Anglila Amaral, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
Chili plants are one of the fruit vegetables that have good business opportunities, the large domestic and foreign demand makes chili a promising commodity. The place for this research is at KWT Karang Lestari, Sibang Kaja Village, Abiansemal District, Badung Regency. This research lasted for 3 months, from October to December 2022. The objectives to be achieved in this study were to determine the marketing channel for chili seeds, determine the marketing costs, marketing margins, farmer share, and the efficiency of the marketing channel for chili seeds in KWT Karang Lestari, Sibang Kaja Village. The data analysis method used is marketing margin analysis, farmer share, and marketing efficiency. The results of this study indicate that there are two marketing channels for chili seeds in KWT Karang Lestari, Sibang Kaja Village, namely : a) Marketing Channel I : Consumer ® Producer, b) Marketing Channel II : Producer ® Trader Retailer ® Consumer. In marketing channel I there are no marketing costs, marketing margins and farmer share. While in the second marketing channel there is a marketing cost of Rp. 500, with a marketing margin of Rp. 1,500 and farmer share of 57.14%. The efficiency of marketing channel I is 0% while the efficiency of marketing channel II is 14.29%. This shows that marketing channel I is more efficiently run than marketing channel II. This happens because marketing channel I does not incur marketing costs